Design of Mechanical Union Peeler Equipment - Arif Rizki Tanjung; Achwil Putra Munir; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The production process that includes pre-harvest until postharvest requires the support of various effective facilities and infrastructure, development equipments and agricultural machinery is among the way of increasing agricultural production. To support this we need a mechanical onion peeler driven by electricity. The study was conducted by literature study and observation on the onion peeler, and then to design the coupling components of the  mechanical onion peeler. The effective capacity of the tool was 14.15 kg / hr. The value of the effective capacity of the tool is larger than the onion peeler driven by human power. Basic costs to be incurred in peeling onions with this tool was Rp. 751,904/kg in the 1st year, Rp.647,531/kg in the 2nd year, Rp. 624,771/kg in the 3rd year, Rp. 613,441/kg in the 4th year, and Rp. 606,609/kg in the 5th year. This tool will reach the break even point when the value has peeling corn amounted to 8624,85 kg/year. Net present value of these tools with an interest rate of 6% Rp. 14.553.501,5 whichmeant that the business was feasible to run. The internalrate of return was 40,93%.   Keywords: design equpments, mechanical peeler, onion.